Revisiting the neuroinflammation hypothesis in Alzheimer’s disease: a focus on the druggability of current targets - Wong-Guerra, Maylin; Calfio, Camila; Maccioni, Ricardo B.; Rojo, Leonel E. (Frontiers in Pharmacology, 2023)
Alzheimer disease (AD) is the most common form of neurodegenerative disease and disability in the elderly; it is estimated to account for 60–70% of all cases of dementia worldwide. The most relevant mechanistic hypothesis to explain AD symptoms are neurotoxicity induced by aggregated amyloid-β peptide (Aβ) and misfolded tau protein. These molecular entities are seemingly insufficient to explain AD as a multifactorial disease characterized by synaptic dysfunction, cognitive decline, psychotic symptoms, chronic inflammatory environment within the central nervous system (CNS), activated microglial cells, and dysfunctional gut microbiota. The discovery that AD is a neuroinflammatory disease linked to innate immunity phenomena started in early nineties by several authors, including the ICC´s group that described in 2004 the role IL-6 in AD-type phosphorylation of tau protein in by deregulating the cdk5/p35 pathway. The “Theory of neuroimmunomodulation”, published in 2008, proposed that the onset and progression of degenerative disease as a “damage signals” phenomena, suggesting the concept of “multitarget” therapy. This theory explains in detail the cascade of molecular event stemming from microglial disorder through the overactivation of the Cdk5/p35 pathway. All these knowledge have led to the rational search of inflammatory targets for natural bioactive molecules or synthetic drugs against AD. The accumulated evidence on increased levels of inflammatory markers in the cerebrospinal fluid (CSF) of AD patients, along with reports describing CNS alterations caused by senescent immune cells in neuro-degenerative diseases, have set out a conceptual framework in which the neuroinflammation hypothesis is being challenged from different angles towards developing new therapies against AD. Moreover, current evidence points to controversial findings in the search for therapeutic candidates to treat neuroinflammation in AD. In this article, we discuss a neuroimmunomodulatory perspective for pharmacological exploration of molecular targets against AD progression, as well as potential deleterious effects of modifying neuroinflammation in the brain parenchyma. We specifically focus on the role of B and T cells, immuno-senescence, drainage of molecules and cells through the brain lymphatic system (BLS), and on the dysfunctional interactions between neurons, microglia and astrocytes. We also proposed a rational framework for identifying “druggable” targets for multi-mechanistic molecules with therapeutic potential